2013
DOI: 10.1097/inf.0b013e31827cd06f
|View full text |Cite
|
Sign up to set email alerts
|

Viral Etiology of Acute Respiratory Infections in Hospitalized and Outpatient Children in Buenos Aires, Argentina

Abstract: HRV were significant pathogens associated with bronchiolitis and pneumonia, especially in hospitalized patients. Both, HRV and coinfections, were risk factors for hospitalization. These findings support the importance of including HRV detection in children with acute respiratory infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
40
1
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 30 publications
17
40
1
10
Order By: Relevance
“…Our findings highlight the fact that three quarters of infants or young children with any respiratory symptoms carry at least one virus. This rate of detection concords with previous studies in developed and African countries [15], [16], [17], [18]. Most of the viruses were identified by molecular diagnosis, and direct immunofluorescence yield was low but concordant with previous work [19], achieving only 10% of positive results.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings highlight the fact that three quarters of infants or young children with any respiratory symptoms carry at least one virus. This rate of detection concords with previous studies in developed and African countries [15], [16], [17], [18]. Most of the viruses were identified by molecular diagnosis, and direct immunofluorescence yield was low but concordant with previous work [19], achieving only 10% of positive results.…”
Section: Discussionsupporting
confidence: 87%
“…It is not yet clear if these multiple viruses identified are all infectious agents. In our study, multiple infections were found with a lower rate (n=4, 2.8%) compared to other studies (10%-43.5%) (14)(15)(16)(17)(18)(19). One of these was association of RV and EV which was diagnosed as URTI and the other three were associations of HBoV and RSV which were diagnosed as LRTI.…”
Section: Discussioncontrasting
confidence: 52%
“…Otros suelen presentar foco evidente, que ya no son sujeto de nuestro estudio: rinovirus, influenza A y B, parainfluenza y adenovirus. 26 Las IBG causadas por E. coli y Streptococcus agalactiae (SGB) son más frecuentes en neonatos. El uso de profilaxis intraparto para prevención de la sepsis por SGB se relacionó con una disminución de la prevalencia de este agente.…”
Section: ¿Cuáles Son Los Agentes Más Frecuentes Relacionados Con Fsf?unclassified